MOTION VERBS EXPRESSING MODES OF MOVEMENT IN ENGLISH AND THEIR VIETNAMESE EQUIVALENTS / Nguyen Thi Ngoc Hien; NHDKH Assoc.Prof.Dr Hoang Tuyet Minh - Nguyen, Thi Ngoc Hien
The purpose of this study is to investigate the syntactic and semantics features of English Motion verbs with reference to Vietnamese equivalent in the English –Vietnamese Dictionary(2008);Vietnamese – English Dictionary(2000). The study is aimed at three point: (1) finding the syntactic and semantics features of the Motion Verbs with reference to Vietnamese equivalent in Dictionary, (2) finding the similarities and differences between the motion verbs in English and their equivalent in Vietnamese and (3) providing some recommendation for the teaching and learning as well as translation of Motion verbs into the target language.This study was designed as a descriptive research with the method of contrastive and componential analysis. According to the data analysis, the result of the study show that the Motion Verbs coincide in their general meaning. However, the Motion Verbs in Vietnamese seems to have much more meanings than that in English. In practice, the study not only supplies some implications to language teaching, learning as well as translating but also raises language users’ awareness of the differences between the Motion Verbs so that they can use them exactly and be successful in their real life communication in English.